Hereditariedade da homeose - Piza Junior, S. de Toledo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1944)
A preliminary account on the normal development of the imaginai discs in holometabolic Insects is made to serve as an introduction to the study of the hereditary homoeosis. Several facts and experimental data furnished specially by the students of Drosophila are brought here in searching for a more adequate explanation of this highly interesting phenomenon. The results obtained from the investigations of different homoeotic mutants are analysed in order to test Goldschmidt's theory of homoeosis. Critical examination of the basis on which this theory was elaborated are equally made. As a result from an extensive theoretical consideration of the matter and a long discussion of the most recent papers on this subject the present writer concludes that the Goldschmidt explanation of the homoeotic phenomena based on the action of diffusing substances produced by the genes, the "evocators", and on the alteration of the normal speed of maturation of the imaginai discs equally due to the activity of the genes, could not be proved and therefore should be abandoned. In the same situation is any other explanation like that of Waddington or Villee considered as fundamentally identical to that of Goldschmidt. In order to clear the problem of homoeosis in terms which seem to put the phenomenon in complete agreement with the known facts the present writer elaborated a theory first published a few years ago (1941) based entirely on the assumption that the imaginai discs are specifically determined by some kind of substances, probably of chemical nature, contained in the cytoplam of the cells entering in the consti- tution of each individual disc. These substances already present in the blastem of the egg in which they are distributed in a definite order, pass to different cells at the time the blastem is transformed into blastoderm. These substances according to their organogenic potentiality may be called antenal-substance, legsubstance, wing-substance, eye-substance, etc. The hipoderm of the embryo resulting from the multiplication of the blastoderm cells would be constituted by a series of cellular areas differing from each other in their particular organoformative capacity. Thus the hypoderm giving rise to the imaginai discs, it follows that each disc must have the same organogenic power of the hypodermal area it came from. Therefore the discs i*re determinated since their origin by substances enclosed in the cytoplasm of their cells and consequently can no longer alter their potentiality. When an antennal disc develops into a leg one can conclude that this disc in spite of its position in the body of the larva is not, properly speaking, an antennal disc but a true leg disc whose cells instead of having in their cytoplasm the antennal substance derived from the egg blastem have in its place the leg-substance. Now, if a disc produces a tarsus or an antenna or even a compound appendage partly tarsus-like, partly antenna-like, it follows tha,t both tarsal and antennal substances are present in it. The ultimate aspect of the compound structure depends upon the reaction of each kind of substance to the different causes influencing development. For instance, temperature may orient the direction of development either lowards arista or tarsus, stimulating, or opposing to the one or the other of these substances. Confering to the genes the faculty of altering the constitution of the substances containing in the cytoplasm forming the egg blastem or causing transposition of these substances from one area to another or promoting the substitution of a given substance by a different one, the hereditary homoeocis may be easily explained. However, in the opinion of the present writer cytoplasm takes the initiative in all developmental process, provoking the chromosomes to react specifically and proportionally. Accordingly, the mutations causing homoeotic phenomena may arise independently at different rime in the cytoplasm and in the chromosomes. To the part taken by the chromosomes in the manifestation of the homoeotic characters is due the mendalian ratio observed in homoeotic X normal crosses. Expression, in itself, is mainly due to the proportion of the different substances in the cells of the affected discs. Homoeotic phenomena not presenting mendelian ratio may appear as consequence of cytoplasmic mutation not accompanied by chromosomal mutation. The great variability in the morphology of the homoeotic characteres, some individual being changed towards an extreme expression of the mutant phenotype while others in spite of their homozigous constitution cannot be distinguished from the normal ones, strongly supports the interpretation based on the relative proportion of the determining substances in the discs. To the same interpretation point also asymetry and other particularities observed in the exteriorization of the phenomenon. In conformity with this new conception homoeosis should not prove homology of Insect appendages (Villee 1942) since a more replacement of substances may cause legs to develop in substitution of the wings, as it was already observed (requiring confirmation in the opinion of Bateson 1894, p. 184) and no one would conclude for the homology of these organs in the usual meaning of the term.